Effect of Conductive Thread and Stitching Parameters on the Sensing Performance of Stitch-Based Pressure Sensors for Smart Textile Applications - Choudhry, Nauman Ali; Shekhar, Ravi; Rasheed, Abher; Arnold, Lyndon; Wang, Lijing (IEEE sensors journal, 2022)
Smart textiles are intelligent fibrous structures that can sense and react to external stimuli. Textile-based sensors can measure physiological and biomechanical signals during daily activities and have a wide range of wearable applications. This paper presents a study on how conductive thread and stitching parameters may influence the sensing performance of stitch-based pressure sensors. The sensors were developed on a lockstitch sewing machine using a multi-filament stainless-steel thread with a different number of plies and twists. Stitching parameters on the machine were also varied to determine their impact on the sensor properties. Electro-mechanical tests were subsequently performed on the developed sensors where a range of pressure was applied to select suitable piezoresistive sensors for their intended applications. Experimental results showed a strong relationship between the sensor fabrication parameters and the sensing properties. Sensors with the working range of 0-58 kPa, sensitivity (0.068 kPa −1 ), response time (75 ms) and recovery time (360 ms) were developed with selected sensor fabrication parameters. The selected sensor was subjected to cyclic loading for up to 5000 cycles to verify its repeatability. The sensor was then embedded into a garment to demonstrate its application potential as a smart wearable on the human subject. Pressure signals and muscle activities were analysed during jogging and cycling. This paper showcases a future direction on how stitch-based sensors can be used for different smart textile applications by varying their fabrication parameters.